2019
DOI: 10.1681/asn.2019010089
|View full text |Cite
|
Sign up to set email alerts
|

GPRC5b Modulates Inflammatory Response in Glomerular Diseases via NF-κB Pathway

Abstract: BackgroundInflammatory processes play an important role in the pathogenesis of glomerulopathies. Finding novel ways to suppress glomerular inflammation may offer a new way to stop disease progression. However, the molecular mechanisms that initiate and drive inflammation in the glomerulus are still poorly understood.MethodsWe performed large-scale gene expression profiling of glomerulus-associated G protein–coupled receptors (GPCRs) to identify new potential therapeutic targets for glomerulopathies. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…GPCR class C group 5 member B (GPRC5B) is an orphan GPCR that belongs to family C of the GPCRs. It is highly expressed in the brain [ 29 , 30 ], adipose tissue [ 31 ] and kidney [ 32 , 33 ]. In an independently generated global knockout mouse line, Gprc5b −/− mice showed behavioral abnormalities [ 26 ], morphological abnormalities in the Purkinje cell axons and disruption of cerebellar synaptic plasticity and motor learning [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPCR class C group 5 member B (GPRC5B) is an orphan GPCR that belongs to family C of the GPCRs. It is highly expressed in the brain [ 29 , 30 ], adipose tissue [ 31 ] and kidney [ 32 , 33 ]. In an independently generated global knockout mouse line, Gprc5b −/− mice showed behavioral abnormalities [ 26 ], morphological abnormalities in the Purkinje cell axons and disruption of cerebellar synaptic plasticity and motor learning [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an independently generated global knockout mouse line, Gprc5b −/− mice showed behavioral abnormalities [ 26 ], morphological abnormalities in the Purkinje cell axons and disruption of cerebellar synaptic plasticity and motor learning [ 34 ]. Additionally, Gprc5b also modulates inflammatory responses in adipocytes [ 31 ], cardiac fibroblasts [ 35 ] and kidney glomeruli [ 33 ]. Consistent with the growth restriction and failure to thrive which we report here, prior studies also showed that loss of Gprc5b protected mice from diet-induced obesity and insulin resistance due to decreased inflammation in white adipose tissue [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified 105 significantly differentially expressed genes in class IV LN where all STRING enrichment clusters identified were involved in NF-κB and apoptosis. Accumulating evidence implicates NF-κB in the pathogenesis of LN including podocyte injury, 25 and NF-κB-mediated cytokine expression has been highlighted in non-response. 19 Variants of several genes in TLR/ NF-κB signalling are associated with LN, including TLR 3/7/9, MYD88, IRAK1, TNFAIP3 and TNIP1 , 26 but this is the first time that NF-κB has been attributed to class IV LN.…”
Section: Discussionmentioning
confidence: 99%
“…We found only three DEGs consistently upregulated (GPRC5b) or downregulated (the pseudogenes Gm4864, Gm10036) throughout the different conditions. Of these, GPRC5b, an orphan G-protein-coupled receptor (GPCR) linked to obesity and inflammation, was deemed as an interesting hit ( Hirabayashi & Kim , 2020; Zambrano et al ., 2019). However, this was not further pursued as we could not validate the GPRC5b upregulation at the protein level using western blot ( data not shown ).…”
Section: Discussionmentioning
confidence: 99%